Examining Adverse Fetal/Neonatal Outcomes Associated With Severe Maternal Morbidity. Issue 3 (September 2021) - Lawton, B.; Filoche, S.; MacDonald, E.J.; Stanley, J.; Meeks, M.; Stone, P.; Storey, F.; Geller, S.E.
Abstract : ( Aust N Z J Obstet Gynaecol . 2020;60:865–870) Severe maternal morbidity (SMM) affects up to 2% of pregnancies worldwide. Up to 40% of SMM may be preventable, and racial and ethnic disparities exist within SMM. Less is known about the effect of SMM on fetal and neonatal outcomes. The aim of this study was to review fetal and neonatal outcomes associated with SMM in pregnancy in New Zealand.